Support and continuity during the first 2 weeks postpartum. Issue 3 (28th April 2014) - Barimani, Mia; Oxelmark, Lena; Johansson, Sven‐Erik; Hylander, Ingrid
<x xml:space="preserve">Abstract</x> Objectives To investigate mothers' perceived satisfaction with support from antenatal care (AC), postpartum care (PC) and child health care (CHC), respectively, during the first two weeks after childbirth. Design Cross‐sectional survey, mixed‐method design. Ethical issues The study was approved by the Regional Research and Ethics Committee at the Karolinska Insititutet, Sweden. Methods Data were collected using a study‐specific questionnaire that focused on mothers' satisfaction with support from AC, PC and CHC during the first 2 weeks after childbirth. All mothers in Stockholm County (n = 546) who gave birth to a live infant during a 1‐week period in 2009 were invited to participate. Descriptive and logistic regression analyses and a content analysis were performed. Results A large discrepancy was found between levels of satisfaction with AC, PC and CHC. Mothers were satisfied with the support from CHC healthcare nurses, but missed follow‐up contact from AC and PC midwives. Nearly 40% of all mothers commented on insufficient support including that continuity in the chain of care was lacking and support for mothers' physical and emotional health was insufficient. Delivery at <37 weeks of gestation was associated with reduced satisfaction with both AC and CHC, but not with PC. Mothers who made emergency visits during the first two weeks were more likely to be dissatisfied with support from PC. Conclusion All links in the chain of care are important for the support of mothers during the first 2 weeks after childbirth, but continuity needs to be improved to raise the quality of care for mothers.